Peranan Leadership Terhadap Disiplin Kerja Karyawan pada PT. Arta Samudra - Isgar Muhammad Ricky Tumoka; Muhammad Arjuna (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The role of leadership is something that is very related to employee work discipline. Meanwhile, work discipline is a benchmark in assessing employee performance in a company. However, at PT. Arta Samudra still has some employees who lack discipline in carrying out their job responsibilities. Among them are coming on time, often abusing the facilities provided. With a qualitative method, this study is aimed at determining the role of leadership in employee work discipline at PT. Arta Samudra, what are the obstacles faced by the leadership to employee performance at PT. Ocean Art. The results obtained are that the role of leadership in employee work discipline is good, but there are still some employees who lack discipline, with the obstacles faced by the leadership, namely the lack of reliable Human Resources and also the special treatment given to employees, and also trying to speak up to all employees about what is expected as their efforts.